A Study of Critical Snarks - de Freitas, Breno; da Silva, Cândida; Lucchesi, Cláudio (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2015)
Snarks are cubic graphs that do not admit a 3-edge-colouring and that are regarded to be the minimal cubic graphs without this property. Snarks have been studied by many researchers throughout the history, since many famous open problems are known to have their potential counter-examples residing in this family of graphs. In this paper we present relations between several classes of critical snarks. It follows from one of such relations that no hypohamiltonian snark is a counter-example to Tutte’s 5-flow Conjecture, thus giving a positive answer to a question proposed by Cavicchioli et al. in 2003.